2019
DOI: 10.1021/acs.analchem.9b00148
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Spectrometry Analysis of Mixed-Breath, Isolated-Bronchial-Breath, and Gastric-Endoluminal-Air Volatile Fatty Acids in Esophagogastric Cancer

Abstract: A noninvasive breath test has the potential to improve survival from esophagogastric cancer by facilitating earlier detection. This study aimed to investigate the production of target volatile fatty acids (VFAs) in esophagogastric cancer through analysis of the ex vivo headspace above underivatized tissues and in vivo analysis within defined anatomical compartments, including analysis of mixed breath, isolated bronchial breath, and gastricendoluminal air. VFAs were measured by PTR-ToF-MS and GC-MS. Levels of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The analysis of the breath samples was done by gas chromatography coupled with mass spectrometry (GC-MS) [ 11 , 13 , 20 , 21 , 22 , 23 ], with solid phase microextraction (SPME), [ 14 , 18 , 22 , 25 ] or with proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS), selected ion flow tube mass spectrometry (SIFT-MS) [ 15 ], proton reaction mass spectrometry (PTR-MS) [ 16 ], or an array of nanosensors [ 22 ]. GC-MS retrofitted with electron ionization (EI) [ 10 ] or retrofitted with positive chemical ionization (PCI) [ 10 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the breath samples was done by gas chromatography coupled with mass spectrometry (GC-MS) [ 11 , 13 , 20 , 21 , 22 , 23 ], with solid phase microextraction (SPME), [ 14 , 18 , 22 , 25 ] or with proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS), selected ion flow tube mass spectrometry (SIFT-MS) [ 15 ], proton reaction mass spectrometry (PTR-MS) [ 16 ], or an array of nanosensors [ 22 ]. GC-MS retrofitted with electron ionization (EI) [ 10 ] or retrofitted with positive chemical ionization (PCI) [ 10 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The collection of exhaled breath was done in containers of 500 mL to 3 L [ 11 , 14 ], but oral cavity air, 20 mL, collected in headspace vials, was also analyzed [ 13 ]. The VOCs concentration levels in breath samples were compared to that in the mixed breath with headspace concentrations, bronchial breath, gastric-endoluminal air [ 14 ], with the highest concentrations being in the gastric-endoluminal air [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Once released into the systemic circulation, VOCs may travel to the lungs where they are excreted in exhaled breath. 10 A systematic review of breath testing for cancer identified distinctive VOCs signals for different tumour sites with pooled sensitivity and specificity of 79% and 89%, respectively (including lung, breast, gastrointestinal, head and neck, prostate and gynaecological tumours). 11 Studies of different gastrointestinal tumour sites also showed different VOC biomarkers for oesophagogastric, pancreatic and colorectal cancers, providing the opportunity for a single breath test to diagnose different cancers based on their unique VOC signature, in a similar way to a single blood draw being used to assess for multiple diseases.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A discriminant function analysis of breath VOC patterns could discriminate CRC vs healthy controls with 85% sensitivity and a 94% specificity (N = 209) [376]. Two recently published studies shown that VOCs have the potential to discriminate esophagogastric cancer patients from heathy controls [377,378]. Another study shows that VOCs can be used for early detection of pancreatic cancer [379].…”
Section: Translational Statusmentioning
confidence: 99%